Pelaksanaan Kegiatan Ekstrakurikuler Drum Band Di SMP Negeri 11 Padang - Arif Rahman Rafendi; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2020)
This type of research in this study was a qualitative with using a descriptive analysis approach that aims to describe the process of implementation of Drum-band extracurricular activity in SMP Negeri 11 Padang. The object of research was Drum band of SMP Negeri 11 Padang. The main instruments of this research were the researcher as an observer, the participants (actor) in an insider position also played a direct role in the object under study. Meanwhile, the supporting instruments used in this study were done by taking documentation from recording device in the form of observation, interview lists and photo camera. The results of the study illustrate that in the implementation of Drum-band extracurricular activity in SMP Negeri 11 Padang, the preparatory step of activitiy begins with the selecting Drum-band members, determining training material, determining training schedules, training and performances. In getting the most out of it, the builder makes two forms of training, which are regular weekly exercises conducted on Saturdays in Personal Development lesson and additional exercises that are done two weeks before Drum-band takes part in competitions or holiday. The first training begins with group musical instrument exercises, then followed by joint training of all musical instruments.